Glucose increases interleukin-12 gene expression and production in stimulated peripheral blood mononuclear cells of type 2 diabetes patients - Wu, Huang-Pin; Chu, Chien-Ming; Kuo, Sheng-Fong; Hua, Chung-Ching; Wu, Shao-Yun; Chuang, Duen-Yau (Biomedical Journal, 2014)
Lipopolysaccharide (LPS)-stimulated peripheral blood mononuclear cells (PBMCs) of type 2 diabetes patients produce more interleukin (IL)-12 under glucose treatment. The aim of this study was to determine whether increased IL-12 response in hyperglycemic LPS-stimulated PBMCs is due to increased gene expression or osmolarity. LPS-stimulated PBMCs of 13 type 2 diabetes patients and 8 healthy controls were used for culture in the presence or absence of glucose or mannitol for 24 h. The IL-12 gene expressions of PBMCs and IL-12 protein levels in supernatants were evaluated. After 24 h, the stimulated PBMCs of diabetes patients expressed more IL-12 mRNA and produced more IL-12 protein following glucose treatment than those without glucose treatment and with mannitol treatment. Stimulated PBMCs of controls did not express more IL-12 mRNA and produce more IL-12 protein following glucose treatment than those without glucose treatment and with mannitol treatment. Glucose increases the IL-12 production in stimulated PBMCs of diabetes patients through increased IL-12 gene expression.